Absence of Germline BRCA1 c.68_69delAG and c.5266dupC Mutations among Hormone Receptor-negative Breast Cancer Patients: A First Impression at a Tertiary Cancer-care Facility in Tanzania - Rweyemamu, Linus P; Akan, Gokce; Mbotwa, Christopher H; Dharsee, Nazima; Namkinga, Lucy A; Lyantagaye, Sylvester L; Mselle, Ted F; Atalar, Fatmahan (Tanzania Journal of Science, 2021)
The germline BRCA1 c.68_69delAG (185delAG) and c.5266dupC (5382insC) mutations are associated with hormone receptor-negative breast cancer (BC). Limited studies have examined their contribution to alarming BC incidence in Sub Saharan Africa (SSA). Our study aimed to examine the contribution of germline BRCA1 c.68_69delAG and c.5266dupC mutations to BC incidence among hormone receptor-negative BC patients admitted to Ocean Road Cancer Institute in Tanzania. Face-to-face interviews were conducted to capture socio-demographic characteristics, anthropometric measurements, family history of cancer and reproductive information from each patient. Their histopathological data were extracted from the hospital medical records. The germline BRCA1 founder mutations were analyzed on blood samples using Sanger sequencing technology. The patients mean age at diagnosis was 47.05 ± 12.82 years. A family history of cancer was observed in 13.6% of patients. The germline BRCA1 c.68_69delAG and c.5266dupC mutations were not detected in the study group. Our findings indicate that the germline BRCA1 c.68_69delAG and c.5266dupC mutations do not contribute to BC manifestation in hormone receptor-negative BC patients in Tanzania. Thus, screening BC patients for these mutations has no clinical relevance. Our data further suggest that the c.68_69delAG and the c.5266dupC mutations should not be considered when developing genetic testing guidelines in Tanzania. Keywords: Breast cancer, germline BRCA1 mutation, c.68_69delAG (185delAG), c.5266dupC (5382insC), Tanzania.